Desain Sistem Mekanik pada Transmisi Motor Matik untuk Keselamatan Pengendara - Sugeng Ariyono; B Supriyo; B Cahyono; DR Harahap (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2019)
The vehicle market in Indonesia, especially motorbikes is very large, it is estimated that the growth of motorbike vehicles will reach 6 million per year. Recently, more than 50 percent is dominated by automatic motorcycles and the market increase significantly. This is because automatic motorcycles can be easily ridden. There are some weaknesses with this transmission system, among them is there is no engine brake when the road is in downhill condition. The motor will easily run when the gas throttle is pressed. This paper discusses the design of a mechanical system on the automatic transmission that is able to prevent mistake on procedures that causes accidents. To achieve this goal, it is necessary to do several steps, including reviewing the existing design, determining the new system, designing the system, manufactured and testing. Experiment results shows that the current motorcycles automatic transmission system can be replaced with a mechatronic system with special linkage mechanism to control ratio change.